Pemahaman Mazhab Sejarah dalam Konteks Kepastian Hukum Hak Ulayat di Indonesia: Studi Kasus terhadap Dinamika Sosial Legal Masyarakat Adat - Pribadi, Ega; Muzqufa, Reagy; Gartiwa, Rinny Purnamasari; Puspitasari, Anggraeni (LPPM Universitas Ekasakti Padang, 2024)
Customary rights are an integral part of the life of indigenous peoples in Indonesia, reflecting the deep connection between people, land, and culture. This study uses the research method of Thomas Aquinas' theory of legal certainty to analyse the legal certainty of customary rights in Indonesia, viewed from the socio-legal perspective of national law and customary law. The research method involves literature review, analysis of laws and regulations, and case studies of land conflicts. The results show that the legal certainty of customary land rights still faces major challenges, including the incompatibility between customary law and national law. In conclusion, the Ministry of Agrarian and Spatial Planning/BPN has an important role in championing customary rights through inclusive policy formulation, official registration of customary land, and fair and transparent resolution of land conflicts. These efforts are essential to ensure effective and sustainable customary rights protection for indigenous peoples in Indonesia.